Workaholism on Job Burnout: A Comparison Between American and Chinese Employees - Cheung, Francis; Tang, Catherine S. K.; Lim, Matthew Sheng Mian; Koh, Jie Min (Frontiers in Psychology, 2018)
Past research frequently reports significant relation between workaholism and job burnout, and some studies further indicate workaholism varies across countries. Surprisingly, there is no study that directly examines whether country moderates the workaholism-burnout association. To address this research question, we have collected independent work samples from two culturally diverse countries, namely the People’s Republic of China and the United States. A total of 2243 participants (1243 American respondents & 1000 Chinese respondents) were recruited. As hypothesized, we found that workaholism significantly predicted job burnout, even when job demand and job autonomy were controlled. Furthermore, moderated regression analyses showed that workaholism related to burnout differently in China and the United States. In particular, when workaholism was low, American respondents reported higher burnout than Chinese respondents. However, when workaholism was high, the difference between Chinese and American was diminished. Implications and limitations were discussed.